AGRESI AMERIKA SERIKAT TERHADAP IRAK PERIODE 2003-2010 - Wulandari, Dewi Ayu; Utama, Tri Cahya; Paramasatya, Satwika (Journal of International Relations, 2015)
United States of America aggression raises many questions about theexplanations on why US aggression against Iraq. The trigger factors todeclare war against Iraq were multifaceted, include: political, economic,ideological, and strategic position. This undergraduate thesis aims tofind the factors that cause aggression of US military forces against Iraqas well as the US government policy toward Iraq which was based on avarious interests. This research analysis uses the theory of realism ininternational relations that based on the pursuit of national interest andnational security. The research concluded that the US aggression to Iraqperiod 2003-2010 was based on the interest of US hegemony in theMiddle East.